EFFECTIVENESS OF THE NATIONAL PUBLIC SERVICE COMPLAINT MANAGEMENT SYSTEM SERVICE PROGRAM (E-LAPOR SP4N) IN THE DEPARTMENT OF COMMUNICATIONS, INFORMATICS AND ENGLISHMENT IN SUKABUMI DISTRICT - Adhar, Fariz; Basori, Yana Fajar F.Y.; Purwanti, Dian (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
In an effort to realize digital technology-based good governance, for public complaint management services related to government performance, the Communication, Information and Signage Office of Sukabumi District launched the E-LAPOR SP4N service program, as one of the public service innovations. The purpose of this study was to determine the effectiveness of the National Public Service Complaint Management System Service Program (E-Lapor SP4N) in responding to and following up on complaints from the public at the Communication, Information and Signage Office of Sukabumi Regency. This research uses qualitative research methods with a descriptive approach to observe individuals or a number of people who will become informants in the phenomenon of research problems. The data collection techniques used were observation, interviews, and documents. Data validation used in this research is source triangulation, technique triangulation, and time triangulation. The results showed that the Communication, Informatics and Standardization Office of Sukabumi Regency successfully implemented the E-Lapor SP4N application strongly. Continuous socialization, training and evaluation efforts were made to ensure understanding and effectiveness of the application. Despite facing resource and budget constraints, the app has successfully increased community participation in the oversight of development and public services. The agency followed clear SOPs in handling complaints, achieving timely resolution despite challenges in responsiveness and budget limitations. The implementation of E-Lapor has had a positive impact with significant improvements in the handling of public complaints, opening up more transparent and participatory access for the community in submitting complaints and aspirations related to public services.